2006
DOI: 10.1177/1477370806059081
|View full text |Cite
|
Sign up to set email alerts
|

Sentencing Outcomes in a Multinational Society

Abstract: A B S T R A C TThe focus of this paper is the effect of nationality on prison disposition in Israel. An interaction between the nationality of the judge, the perpetrator and the victim is examined. The data were collected in the northern district courts in Israel and consist of 1394 court records. The results show that being an Arab defendant is an inherent liability in the Israeli criminal justice system -they are more likely than Jews to receive prison sentences. Arab judges seem to be more punitive than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In the study, 84.3 percent of the Jewish victims were victimized by Jewish offenders, and 90.1 percent of he Arab victims were victimized by Arabs. As has been shown previously (Fishman, Rattner, & Turjeman, 2006), being a member of a minority group increases a defendant's likelihood of being convicted.…”
Section: Discussionsupporting
confidence: 55%
“…In the study, 84.3 percent of the Jewish victims were victimized by Jewish offenders, and 90.1 percent of he Arab victims were victimized by Arabs. As has been shown previously (Fishman, Rattner, & Turjeman, 2006), being a member of a minority group increases a defendant's likelihood of being convicted.…”
Section: Discussionsupporting
confidence: 55%
“…This discrimination is manifested in policing, sentencing, and punishment (Baumgartner, 2016 ; Sklansky, 2017 ). In Israel, such discrimination has been documented regarding, in particular, the ethnic Arab minority (Fishman et al, 2006 ; Haklai, 2013 ; Hasisi & Weitzer, 2007 ; Shayo & Zussman, 2016 ). To the best of my knowledge, no studies have yet examined the role of discrimination in judicial decisions on insanity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the criminal justice system, Gazal‐Ayal and Sulitzeanu‐Kenan (2010) found evidence of in‐group bias in decisions by Arab and Jewish judges to detain suspects (but not, it should be noted, with regard to the length of detention). Both Fishman et al (2006) and Rahav et al (2015) found that under similar circumstances, judges sentenced Arab defendants to harsher penalties than their Jewish counterparts for similar offenses; and Grossman et al (2016) showed that while appeal outcomes for Jewish defendants were independent of the judges' ethnicity, Arab defendants received more lenient punishment when there was at least one Arab judge on the panel, compared to a panel composed exclusively of Jewish judges.…”
Section: Theory and Hypothesesmentioning
confidence: 99%